2020
DOI: 10.1186/s13075-020-02317-6
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy occurs in lymphocytes infiltrating Sjögren’s syndrome minor salivary glands and correlates with histological severity of salivary gland lesions

Abstract: Backgrounds The organization of minor salivary glands (MSG) infiltrates, in patients with Sjögren’s syndrome (SS), associates with disease severity and progression. Aberrant regulation of lymphocyte autophagy is involved in autoimmunity, and in previous work, we provided the first evidence of upregulated autophagy in CD4+ T cells infiltrating SS MSG. The aim of this study was to further explore autophagy in SS infiltrating and circulating lymphocytes and to investigate its role in disease histopathological pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
0
10
0
4
Order By: Relevance
“…The pathologic role of autophagy in the lymphocyte infiltration of exocrine glands, as well as in the survival and activation of epithelial cells in the salivary gland has previously been described in pSS ( 3 ). Colafrancesco et al ( 3 , 40 , 41 ) demonstrated that up-regulated autophagy pathways induced by inflammation activate salivary gland epithelial cells in pSS, causing the high expression of adhesion molecules, and it is associated with histologic severity. This study discovered hub genes of autophagy in pSS, including PIK3CA, STAT1, MAPK3, and MTOR.…”
Section: Discussionmentioning
confidence: 99%
“…The pathologic role of autophagy in the lymphocyte infiltration of exocrine glands, as well as in the survival and activation of epithelial cells in the salivary gland has previously been described in pSS ( 3 ). Colafrancesco et al ( 3 , 40 , 41 ) demonstrated that up-regulated autophagy pathways induced by inflammation activate salivary gland epithelial cells in pSS, causing the high expression of adhesion molecules, and it is associated with histologic severity. This study discovered hub genes of autophagy in pSS, including PIK3CA, STAT1, MAPK3, and MTOR.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we have investigated autophagy in the pathogenesis of primary SS focusing on lymphocytes infiltrating minor SGs (38,39). In the present study, we investigated the role of autophagy in the survival and activation of SGECs, which represent the main constituent of the SG microenvironment and the pivot of “autoimmune epithelitis” in primary SS.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy flux was also measured by flow cytometry by using the Cyto-ID™ Autophagy Detection Kit (Enzo Life Science) as previously described ( Colafrancesco et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Autophagy flux was also measured by flow cytometry by using the Cyto-ID ™ Autophagy Detection Kit (Enzo Life Science) as previously described (Colafrancesco et al, 2020). Briefly, FLS were pelleted and then resuspended in DMEM without phenol red, supplemented with 10% FBS, and diluted Cyto-ID solution.…”
Section: Analysis Of Autophagymentioning
confidence: 99%